The satire of the Salonnière: women and humour in Seventeenth-Century France - Nicholson, A (Liverpool University Press, 2022)
This article reassesses styles of humour in the literary output of seventeenth-century French salons by attending to women and satire. While scholarship has repeatedly dwelt on salons and salon hostesses as objects of satire, this study argues that salon hostesses were also writers of satire, and importantly writers of satire aimed at would-be hostesses, via an analysis of Madeleine de Scudéry’s Artamène; ou, Le Grand Cyrus (1649–1653). In the “Histoire de Sapho” (Book II, Tome X of Artamène), Scudéry presents a satirical portrait of an “anti-salonnière” named Damophile. This wannabe salon hostess strives to imitate the titular salonnière, Sapho, and become a well-respected savante, but instead appears excessive and pedantic in her efforts, attracting the ridicule of Sapho and her circle. Drawing together modesty, mockery and collective amusement, Scudéry uses satire to provide a model for other women writers that is firmly reconciled with the honnête values of salon culture.